A sequencia Fedathi para uma aprendizagem significativa da função afim: uma proposta didática com o uso do software geogebra - Souza, Antônio Marcos de (2015)
In the scenario of the Brazilian Public School, every generation of education workers that join in the teaching of Mathematics becomes even more challenging. Consequently, large-scale assessment indicators unveil undesired results relating to learning processes. Considering that, the present work shows a proposal of teaching Affine Function, structured from the assumption of Meaningful Learning Theory and from the methodological proposal of teaching Fedathi Sequence, using as an auxiliary technological resource the software Geogebra. The research was directed to students of the first grade of high school of a State Public School in Ceará, Brazil. The goal was offer conditions for students, beginning with pre-arranged activities, to build the concept of Affine Function, starting from a problem and, after that, have a clue of this concept by doing simulations in the Geogebra environment, taking the first role in this process. As a methodological procedure of investigation, didactic sessions were achieved, which are classes structured from an environmental and theoretical analysis, following the step of Fedathi Sequence (positioning, maturation, solution and test) that also were considered the programmatic principles of the content (Progressive Differentiation, Integrative Reconciliation, Organizational Sequence and Consolidation) and the Conceptual Maps. During the process of construction and differentiation of concepts by students, the researcher teacher took the so called “hands-in-the-pocket attitude”, avoiding give prepared answers to students’ questions. The results of qualitative analyses of the didactic sessions and quantitative of pre-test, after-test and questionnaires reveal that: students experienced the process of construction of the concept, taking independent attitude in relation to his/her learning process.; The learned content was represented in a substantive way; The software Geogebra and the conceptual maps facilitated the Progressive Differentiation of the concept of Affine Function, as well as the Integrative Reconciliation of specifications of this concept. Students did not know the software Geogebra, and do not even know another software to study functions before this proposal; the majority of the students successfully learned the exploited concepts. Concluding, the new challenges of learning moves the 21st century teachers to a continuous enrichment of the pedagogic practices from the theories, methodologies and the pedagogic usage of technological resources integrates to the scholar curriculum.